Resposta da mamoneira a doses de potássio, boro, zinco, cobre, magnésio e a fontes de nitrogênio - Diógenes, Talita Barbosa Abreu (2012)
The production of castor bean in the Apodi Plateau can be used as an alternative to crop rotation schemes aimed at economic and environmental sustainability of areas traditionally cultivated cucurbits. For the castor produce satisfactorily, the adaptation to climate conditions and the use of appropriate farming is essential to have supplies of water and nutrients. In alkaline soils, the availability of some nutrients become limited, especially micronutrients; nitrogen, when applied in this type of soil can be quickly lost to the atmosphere by volatilization of ammonia, and the main occurrence of this loss occurs with the use of urea. This work aimed to evaluate the response of castor bean doses of potassium, boron, zinc, copper, magnesium and nitrogen sources applied at planting and coverage in order to contribute to the improvement of its productive system in the Apodi Plateau . In experiment 01, 10 treatments were compared regarding the soil application of five doses of potassium (0, 25, 50, 75 and 100 kg ha-1) and five doses of boron (0.0, 0.5, 1.0, 2.0 and 3.0 kg ha-1). In experiment 02, compared to seven treatments with the aim of evaluating the effects of the presence and absence of fertilization with Zn, Cu and Mg and the effects of forms of use (cultivation and or coverage) of N sources (urea and , or, ammonium sulfate). At 47 days after emergence composite samples were collected at depth 0-20 cm from the floor area of each plot, to determine the levels of K, Zn, Cu and Mg available. At the beginning of flowering of castor beans was assessed the nutritional status of plants, determining the K, B, Zn, Cu, Mg, S and N in the leaves. At the end of the experiment were evaluated: plant height, height of insertion of the primary raceme, stem diameter, number of racemes per plant, thousand grain weight of the raceme and primary and subsequent productivity. Under the experimental conditions, the average productivity of castor beans was 2.019 kg ha-1 grain, without requiring fertilization with potassium, boron, copper, zinc and magnesium, and indiscriminately using urea or ammonium sulfate as nitrogen source for crop fertilization and or cover, incorporated into the soil 5 cm in depth